(untitled) (Journal of Mining and Metallurgy, Section B: Metallurgy, 2019)
In this paper, a thermodynamic re-assessment of the Al-Sn-Zn ternary system was performed by means of the CALculation of PHAse Diagram (CALPHAD) approach. The thermodynamic descriptions of the binary Al-Sn, Al-Zn and Sn-Zn systems from the literature were directly adopted, and the newly reported experimental phase equilibria, enthalpies of mixing and activities of Al in the ternary liquid phase were taken into account. A set of self-consistent thermodynamic parameters for the ternary Al-Sn-Zn system were finally obtained. A comprehensive comparison between the presently calculated phase equilibria/thermodynamic properties and the experimental data indicates that the present thermodynamic descriptions of the ternary Al-Sn-Zn system show very good agreement with most of the experimental data. The further direct comparison with the calculated results due to the previous assessment demonstrates that a significant improvement was achieved by the present assessment though fewer ternary interaction parameters were utilized.